An Investigation of Cohesion and Rhetorical Moves in Thesis Abstracts - L Luthfiyah; A Alek; F Fahriany (IJEE (Indonesian Journal of English Education), 2015)
This study aimed at investigating cohesion and rhetorical moves in thesis abstracts of English Education students. This study employed a qualitative research design in which 10 abstracts were chosen as samples. The cohesion is analyzed based on Halliday's and Hasan's  concept while rhetorical moves are analyzed based on Swales' and Feak's framework. The results show that all cohesive devices are used except substitution. Among those devices, reference is the most frequently used. The results also show that some cohesive devices are used incorrectly. As a result, seven abstracts (70%) are still in medium category of cohesion level while three abstracts (30%) are in high category of cohesion level. Furthermore, 7 abstracts are organized in different move patterns which do not follow the Swales' and Feak's framework. From the results of the study, it can be concluded that most of the abstract samples achieve medium category level of cohesion, and the rhetorical moves in most of the abstracts samples are not organized well. Permalink/DOI: http://dx.doi.org/10.15408/ijee.v2i2.3086